Acute Postcesarean Pain Is Associated With In-hospital Exclusive Breastfeeding, Length of Stay, and Postpartum Depression. Issue 4 (December 2020) - Babazade, R.; Vadhera, R.B.; Krishnamurthy, P.; Varma, A.; Doulatram, G.; Saade, G.R.; Turan, A.
Abstract : ( J Clin Anesth . 2020;62:109697) In 2011, 79% of newborns in the United States were breastfed, but by 6 months of age, only 49% of these were still breastfed [in accordance with the CDC recommendation of exclusive breastfeeding (EBF) for at least 6 mo]. By 12 months, a mere 27% of infants born in 2011 were still breastfed. Higher risks exist for infants not EBF for 6 months, in comparison with those EBF, including gastrointestinal infections, atopic eczema, respiratory illness, type II diabetes, obesity later in life, and leukemia. Six months of EBF is estimated to prevent one tenth of child deaths, but also to reduce child and mother medical costs by $3 billion each year. As breastfeeding within the first postdelivery hour is an important predictor for the success of EBF, this study's aim was to investigate the association between postoperative pain and breastfeeding during hospital stay following cesarean delivery to determine any factors that may prevent successful EBF.